Problems of Notary Responsibility for Compliance with Company Capital - Satrio, Muh.; Fajar Riyanto, Taufan (TABELLIUS: Journal of Law, 2026)
The practice of establishing a Limited Liability Company in reality still shows a discrepancy between the authorized capital and the issued and paid-up capital as stated in the deed of establishment. This condition has the potential to give rise to legal issues related to the validity of the deed and the responsibility of the Notary as a public official authorized to make authentic deeds. This study aims to analyze the responsibility of the Notary in the process of establishing a Limited Liability Company if there is a capital discrepancy, examine its legal implications for the validity of the deed, and identify forms of legal protection for the parties and third parties. This study uses a normative legal method with a statutory, conceptual, and case approach. Legal materials were obtained through literature studies and analyzed qualitatively using deductive reasoning. The results of the study indicate that the Notary is professionally, ethically, and legally responsible for ensuring the formal accuracy of the capital data in the deed, even though the material obligation to deposit lies with the shareholder. Capital discrepancies can cause administrative defects and open up the possibility of civil and ethical liability if negligence is proven. This study concludes that strict implementation of the principle of prudence by Notaries is the key to ensuring legal certainty and protection in the establishment of Limited Liability Companies.